Micrognathia and Oropharyngeal Space in Patients With Robin Sequence: Prenatal MRI Measurements - Kooiman, Tessa D.; Calabrese, Carly E.; Didier, Ryne; Estroff, Judy A.; Padwa, Bonnie L.; Koudstaal, Maarten J.; Resnick, Cory M. (Journal of oral and maxillofacial surgery, 2018)
Micrognathia is the initiating feature of Robin sequence (RS) and leads to airway obstruction. Prenatal identification of micrognathia is currently qualitative and has not correlated with postnatal findings in previous studies. Oropharyngeal airway space has not been evaluated prenatally. The purposes of this study were to 1) quantitate mandibular characteristics and oropharyngeal size at prenatal magnetic resonance imaging (MRI) and 2) identify differences in fetuses with postnatal RS compared with those with micrognathia (without RS) and normal controls. This is a retrospective case-control study of fetuses with prenatal MRIs performed from 2002 through 2017 who were live born and evaluated postnatally for craniofacial findings. Postnatal findings were used to divide patients into 3 groups: 1) RS (micrognathia, glossoptosis, and airway obstruction), 2) micrognathia without RS (“micrognathia”), and 3) a gestational-age matched control group with normal craniofacial morphology (“control”). Inferior facial angle (IFA), jaw index, and oropharyngeal space (OPS) were calculated and compared among groups. Of 116 patients in this study, 27 had RS (23%), 35 had micrognathia (30%), and 54 were control subjects (47%). IFA, jaw index, and OPS were statistically significantly smaller in the RS group compared with the comparison groups (P < .0001). Prenatal MRI measurements of micrognathia and OPS are considerably different in patients with RS compared with other groups, including those with micrognathia alone. These measurements might serve as reliable prenatal predictors of RS.